Time headway study on exclusive motorcycle lane - Yuen, C.W. (2011)
Malaysia is facing high motorcyclist fatalities each year. Motorcycles constitute more than half the total vehicles and contribute more than 47% of casualties (deaths and serious and slight injuries) in traffic crashes. Thus, safety of this form of transportation is an important issue. One of the problems that traffic engineers face all this while is that there is no international standard for motorcycle track design. This preliminary study was conducted on two different traffic geometry designed for the exclusive motorcycle lane. The sites chosen are a straight section of motorcycle lane and a stretch which leads to a tunnel. The time headways were taken for these sites at three different periods of time. ANOVA analyses were applied on the time headway and the factors that affect the variation of time headway at motorcycle lane were studied.